Overview of hepatocarcinogenesis focusing on cellular origins of liver cancer stem cells: a narrative review - Jong Ryeol Eun (Journal of Yeungnam Medical Science)
Hepatocellular carcinoma (HCC) accounts for 85% to 90% of primary liver cancers and generally has a poor prognosis. The hierarchical model, which posits that HCC originates from liver cancer stem cells (CSCs), is now widely accepted, as it is for other cancer types. As CSCs typically reside in the G0 phase of the cell cycle, they are resistant to conventional chemotherapy. Therefore, to effectively treat HCC, developing therapeutic strategies that target liver CSCs is essential. Clinically, HCCs exhibit a broad spectrum of pathological and clinical characteristics, ranging from well-differentiated to poorly differentiated forms, and from slow-growing tumors to aggressive ones with significant metastatic potential. Some patients with HCC also show features of cholangiocarcinoma. This HCC heterogeneity may arise from the diverse cellular origins of liver CSCs. This review explores the normal physiology of liver regeneration and provides a comprehensive overview of hepatocarcinogenesis, including cancer initiation, isolation of liver CSCs, molecular signaling pathways, and microRNAs. Additionally, the cellular origins of liver CSCs are reviewed, emphasizing hematopoietic and mesenchymal stem cells, along with the well-known hepatocytes and hepatic progenitor cells.